2021
DOI: 10.1002/eqe.3514
|View full text |Cite
|
Sign up to set email alerts
|

Seismic control performance of a three‐story frame prototype equipped with semi‐active variable stiffness and damping structural joints

Abstract: This paper presents numerical and experimental studies on semi‐active seismic response control of structures equipped with variable stiffness and damping structural joints. Such adaptive joints, which are comprised of a shape memory polymer (SMP) core reinforced by an SMP‐aramid composite skin, function as load‐transfer components as well as semi‐active control devices. The SMP core material can transition from a glassy to a rubbery state through thermal actuation resulting in a shift of the structural natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In addition, prefabricated beams and columns are adjacent, and are connected by prefabricated beam-column joints. As a result, the joints of prefabricated beams and columns play an irreplaceable role in the overall structural load-bearing performance, structural stiffness, and seismic behavior of buildings [5]. A common building design in China utilizes cast-in and shelf connections to connect the primary and secondary beams, whereas the reasonable design of the prefabricated joints is also crucial to the overall seismic performance of the structure.…”
Section: Analysis On Different Joints Of Prefabricated Buildingsmentioning
confidence: 99%
“…In addition, prefabricated beams and columns are adjacent, and are connected by prefabricated beam-column joints. As a result, the joints of prefabricated beams and columns play an irreplaceable role in the overall structural load-bearing performance, structural stiffness, and seismic behavior of buildings [5]. A common building design in China utilizes cast-in and shelf connections to connect the primary and secondary beams, whereas the reasonable design of the prefabricated joints is also crucial to the overall seismic performance of the structure.…”
Section: Analysis On Different Joints Of Prefabricated Buildingsmentioning
confidence: 99%
“…To achieve this transformation, it is assumed that the inputs and outputs associated with Step1 have the same cumulative distribution function (CDF). This assumption is formulated in (6). To achieve this transformation, it is assumed that the inputs and outputs associated with Step1 have the same cumulative distribution function (CDF).…”
Section: Probabilistic Constraint Transformation To Standard Normal S...mentioning
confidence: 99%
“…Active structural control through sensing and actuation has been considered as a solution for meeting safety and serviceability criteria in the presence of severe loading events such as high winds and large crowds [5]. The authors demonstrated in [6] that semi-active building control may be employed to reduce the structure's reaction to seismic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…In (Senatore and Reksowardojo 2020) it has been shown that well designed adaptive structures can achieve up to 60% reduction of the whole-life energy (material + operational for actuation) compared to optimized passive structures. Semi-active control through thermal actuation of variable stiffness and damping joints were investigated to significantly reduce the dynamic response of a 1:10-scale multi-story building under earthquake loading (Wang et al, 2021). Adaptive façades have been investigated at different universities over the last years (Loonen et al, 2013;Bedon et al, 2019a;Bedon et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%